Sozialklauseln im internationalen Handel: wirtschaftsethische Kriterien - Stückelberger, Christoph (Aussenwirtschaft, 1996)
The globalisation of the world economy and the liberalisation of the world trade intensified the debate on minimum social standards in the production of goods and on social clauses in trade agreements. The author first summarises the actual positions in the international discussion on the subject. He then develops ten ethical criteria as an orientation to judge social clauses. They include basic values like human rights as well as the relation between economic and social development. (Aussenwirts Zürich/SWP)